"Portugal's Public Opinion in the Context of Austerity: The Curious Case of Healthcare" - Tamara; Simone Schneider; Asensio, M. (24th International Conference of Europeanists, 2017)
Portuguese healthcare system during the recent economic crisis are associated with changes in public evaluations of healthcare. We conduct regression analyses of cross-sectional data from the seven rounds of the European Social Survey of 13,271 individuals living in private households in Portugal. In line with our expectations, we find healthcare evaluations to increase until 2010 and to drop in 2011/12, when public healthcare spending were reduced and a number of health policy measures in response to the Memorandum of Understanding in May 2011 were introduced. Healthcare evaluations of vulnerable subgroups (i.e. older and retired individuals, individuals with poor health status, and low income, and education) dropped particularly strongly. We also find more pronounced differences in healthcare evaluations between certain subgroups (i.e. health status and income groups) after 2011. Surprisingly, healthcare evaluations increased in 2015 despite ongoing reform processes. Our findings contribute to the literature on the effect of austerity on public welfare attitudes and stress the need to analyze the differential impact of crisis-induced welfare state changes across social groups.